Disentangling potential genotypes for macro and micro nutrients and polymorphic markers in Chickpea - Neha Mittal; Juhi Bhardwaj; Shruti Verma; Rajesh Kumar Singh; Renu Yadav; D. Kaur; Akshay Talukdar; Neelam Yadav; Rajendra Kumar (Scientific Reports, 2023)
Abstract The present investigation was conducted to assess the nutritional diverseness and identify novel genetic resources to be utilized in chickpea breeding for macro and micro nutrients. The plants were grown in randomized block design. Nutritional and phytochemical properties of nine chickpea genotypes were estimated. The EST sequences from NCBI database were downloaded in FASTA format, clustered into contigs using CAP3, mined for novel SSRs using TROLL analysis and primer pairs were designed using Primer 3 software. Jaccard’s similarity coefficients were used to compare the nutritional and molecular indexes followed by dendrograms construction employing UPGMA approach. The genotypes PUSA-1103, K-850, PUSA-1108, PUSA-1053 and the EST-SSR markers including the 5 newly designed namely ICCeM0012, ICCeM0049, ICCeM0067, ICCeM0070, ICCeM0078, SVP55, SVP95, SVP96, SVP146, and SVP217 were found as potential donor/marker resources for the macro–micro nutrients. The genotypes differed (p < 0.05) for nutritional properties. Amongst newly designed primers, 6 were found polymorphic with median PIC (0.46). The alleles per primer ranged 1 to 8. Cluster analysis based on nutritional and molecular diversities partially matched to each other in principle. The identified novel genetic resources may be used to widen the germplasm base, prepare maintainable catalogue and identify systematic blueprints for future chickpea breeding strategies targeting macro–micro nutrients.